Moral Dilemmas and Negotiations in a Relationship: A Performance Study - Regmi, Aarati (JODEM: Journal of Language and Literature, 2023)
A Separation, a family drama, reflects the struggle and negotiations within people's life. The film revolves around a middle-class Tehran couple's disagreement over where and how to live and move further leads to the growing conflict. Nader and Simin's partial split becomes only one of the reasons that push the whole family into a problem. The story quietly and cleverly combines elements of family melodrama and legal thriller. With a textual analysis, this paper addresses the performance strategies of characters, besides, the movie captures the frustrations of city life; it reflects not only the modern Iranian life but every everyday life of the globe. So, this paper studies the film from Ervin Goffman's dramaturgical approach as it finely embraces human-restored behavior that includes conflict, relationships, secrets, and other elements in everyday life. It also emphasizes the way people present themselves in front and backstage of their everyday life. However, it displays peoples’ performance in their daily relationships and how they react toward it. Furthermore, this paper depicts and reflects that every family adheres to moral dilemmas and relationship negotiations, yet it is complex and multi-faceted.